Turismo de aventura y oferta turística en la parroquia achupallas, cantón Alausí - Cajilema Yaguachi, Fanny Lorena (2022)
RESUME The general objective of this research was to analyze how Adventure Tourism influences the Tourist Offer in the Achupallas Parish, Alausí Canton, for this a descriptive methodology was used because the description of the variables was made, both the independent one that is "adventure tourism" as the dependent that is "tourist offer", a cross-sectional non-experimental investigation of correlational type was carried out, using surveys as a technique to collect information, for which questionnaires were used as an instrument, these were valued by means of of the Likert scale. The study population was selected through the non-probabilistic method with selection sampling, where the researcher was able to select the individuals that represent the population, based on a subjective judgment, for the sample tourists and professional experts were considered. of adventure tourism, the questionnaire was carried out based on the variables, made up of 10 items. As a result of this investigation, a value of 0.000 was obtained in the verification of the hypothesis, that is, less than the significance value that is 0.05, thus rejecting the null hypothesis and approving the alternative hypothesis that adventure tourism modalities influence the Tourist Offer in the Achupallas Parish, Alausí Canton. Finally, it was possible to conclude as a proposal for this research the design of an interpretive trail to promote hiking activity in the Ozogoche lagoon. Keywords: Tourism, adventure, sport, regulation, offer